Impact Evaluation of SDG-Driven Solutions: An Analysis of Economic-Social-Environment Solutions and Return on Value (ROV) - Puteh, Fadilah; Wan Abdul Halim, Wan Puspa Melati; Ali, Affezah; Tuan Ismail, Tuan Nooriani (Journal of Technical Education and Training, 2024)
The 17 Sustainable Developmental Goals (SDGs) initiatives have widely been implemented at both local and national levels throughout Malaysia. At local level, the impact evaluation of these initiatives is required to be carried out to validate its effectiveness of these community-based projects (CBPs) for their beneficiaries. In 2023, Selangor, the sole state in the Central two region, underwent impact evaluations for 19 community-based projects (CBPs) funded and monitored by the All-Party Parliamentary Group Malaysia - Sustainable Development Goals (APPGM-SDG). Employing a mixed-method approach integrating qualitative and quantitative methodologies, the evaluations drew data from project documents (including proposal, monthly and final reports), focus group discussion (FGDs) and site visit observation. Findings gathered from solution providers, project beneficiaries and evaluators observation were triangulated to provide a comprehensive understanding of the impact of the solution projects based on the three dimensions namely i) Economic-Social-Environment (Ec-S-Ev) Solutions, ii) Return on Value (ROV) Dimension, as well as iii) Impact Evaluation (IE) on six domains. The domains include Deep (Personal), Clear (Skills), Wide (Network), High (System), SDGs, and Gender. In the analysis of (Ec-S-Ev) solution, this paper emphasis on income generation which showcases the significant need for economic empowerment and promoting sustainable livelihoods to tackle poverty, especially urban poverty. Finding highlights 18 projects focused on providing economic solution through CBPs and two dimensions namely Deep, and Clear recorded high mean scores than the other four dimensions measured in this impact evaluation exercise. This research contributes to the field of project impact evaluation and provides valuable insights for practitioners, policymakers, and organizations striving to create sustainable development and uplift communities in Malaysia and beyond